Beyond artificial intelligence : from human consciousness to artificial consciousness - Cardon, Alain, 1946- (London, UK : ISTE, Ltd. ; Hoboken, NJ : John Wiley & Sons, Inc., 2018)
This book will present a complete modeling of the human psychic system that allows to generate the thoughts in a strictly organizational approach that mixes a rising and falling approach. The model will present the architecture of the psychic system that can generate sensations and thoughts, showing how one can feel thoughts. The model developed into an organizational architecture based on massive multiagent systems. The architecture will be fully developed, showing how an artificial system can be endowed with consciousness and intentionally generate thoughts and, especially, feel them. These results are multidisciplinary, combining both psychology and computer science disciplines.
2.9. The representation of the things and the apprehension of temporality2.10. Multisystem deployment; 2.11. The final fate of systems endowed with artificial consciousness; Conclusion; Bibliography; Index; Other titles from iSTE in Computer Engineering; EULA.
Includes bibliographical references.
Online resource; title from PDF title page (EBSCO, viewed September 04, 2018).
John Wiley and Sons
Keywords: Conscious automata; Consciousness; Consciousness; Machines intelligentes; Conscience; COMPUTERS -- General; Conscious automata; Consciousness